The Effect of Entrepreneurship on Salt Business Performance in Jeneponto District, South Sulawesi - Aswar; Burhanuddin; Suprehatin (Jurnal Manajemen & Agribisnis, 2022)
Salt is one of the strategic commodities as a component of human nourishment and raw material for sustainable industries. Like other agriculture and food business, developing entrepreneurial skills and behavior among salt producers is very important. This study aims to describe the characteristics of salt producers and examine the effects of entrepreneurial behavior on salt business performance. This study used a primary data of 120 salt producers in Jeneponto regency. The data were analyzed using Microsoft Excel and Partial Least Square-Structural Equation Model (PLS-SEM). The results showed that salt farmers in Jeneponto Regency had entrepreneurial characteristics seen from their experience and motivation in doing business. Entrepreneurial behavior had a positive and significant effect on the performance of the salt business. In addition, individual characteristics also have a positive and significant effect on entrepreneurial behavior, but the environment has no significant effect on salt entrepreneurial behavior in Jeneponto Regency. This study implies that improving entrepreneurial behavior of salt produces in Jeneponto Regency will increase their salt business performance. Keywords: business performance, entrepreneurial behavior, PLS-SEM, salt